ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN POLEWALI MANDAR - ANDI ISMAWATY; HASANUDDIN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Service quality always emphasizes the focus on meeting customer expectations, namely the community. In this study, service quality is the focus of efforts to influence community satisfaction. This study uses a quantitative approach with survey data collection procedures located at the Polewali Mandar Regency Population and Registry Office. The measurement scale used is the Likert scale, in which the number of samples is determined using the Slovenian formula with a penetration value of 10%, so that 95 samples from 985 populations in the area of ​​the Population and Registry Office, Polewali Mandar Regency, are obtained. This study produced results based on concurrent tests, concluding that of the five variables, consisting of physical evidence (X1), reliability (X2), responsiveness (X3), guarantee (X4) and empathy (X5), the Community satisfaction. yields 0.867 during the pre-test, which means that the quality of service is largely influenced by the independent variable, which is 86.7% and physical evidence (X1), reliability (X2), responsiveness (X3), guarantee (X4), and empathy (X5) and the remaining 13.3% are influenced by other variables that were not examined in this study.